If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b(b + -2) = b Reorder the terms: b(-2 + b) = b (-2 * b + b * b) = b (-2b + b2) = b Solving -2b + b2 = b Solving for variable 'b'. Reorder the terms: -2b + -1b + b2 = b + -1b Combine like terms: -2b + -1b = -3b -3b + b2 = b + -1b Combine like terms: b + -1b = 0 -3b + b2 = 0 Factor out the Greatest Common Factor (GCF), 'b'. b(-3 + b) = 0Subproblem 1
Set the factor 'b' equal to zero and attempt to solve: Simplifying b = 0 Solving b = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b = 0Subproblem 2
Set the factor '(-3 + b)' equal to zero and attempt to solve: Simplifying -3 + b = 0 Solving -3 + b = 0 Move all terms containing b to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + b = 0 + 3 Combine like terms: -3 + 3 = 0 0 + b = 0 + 3 b = 0 + 3 Combine like terms: 0 + 3 = 3 b = 3 Simplifying b = 3Solution
b = {0, 3}
| 2x-6y= | | n^2=10n+3000 | | -56+[-14]=4x+5 | | .12x+.16y=6 | | l(x)-l(x+5)=0 | | 0.28x-1.2= | | 3a^3+a^2=2a | | 2.4+0.4x= | | 35+w^2=12w | | lo(x)-lo(x+5)=0 | | 600=10c+5s | | 3n=12+n+26 | | -4x+30=3x-10 | | -5x-2=3 | | 0.28x-10-1.2= | | -4x+30=13x-10 | | x^2+kx+30=x^2+3x-10 | | 2.4+0.4x-10= | | 0=a^2-6a-100 | | -12+24y=-60 | | logx-log(x+5)=0 | | 2.4+0.4x-30= | | 4x-.8=2.2 | | 13x+1=11t+9 | | -16=8h-4h | | 29=x-44 | | x^2-4x+7=7 | | (-7)(-14)0.7= | | 4x+.8=2.2 | | Y=4(2x+7) | | -3f-7-8f=16 | | 169-(56+67)= |